With God on their Side Sport in the service of religion - Magdalinski, Tara; Chandler, Timothy John Lindsay 1952- (Taylor and Francis, 2002)
'Sport' and 'religion' are cultural institutions with a global reach. Each is characterised by ritualised performance and by the ecstatic devotion of its followers, whether in the sports arena or the cathedral of worship. This fascinating collection is the first to examine, in detail, the relationship between these two cultural institutions from an international, religiously pluralistic perspective. It illuminates the role of sport and religion in the social formation of collective groups, and explores how sport might operate in the service of a religious community. The book offers a series of cutting-edge contemporary historical case-studies, wide-ranging in their social and religious contexts. It presents important new work on the following fascinating topics: * sport and Catholicism in Northern Ireland * Shinto and sumo in Japan * women, sport and the American Jewish identity * religion, race and rugby in South Africa * sport and Islam in France and North Africa * sport and Christian fundamentalism in the US * Muhammad Ali and the Nation of Islam. With God on their Side is vital reading for all students of the history, sociology and culture of sport. It also presents important new research material that will be of interest to religious studies students, historians and anthropologists